Examination of Athlete Triad Symptoms Among Endurance-Trained Male Athletes: A Field Study - Moore, Erin M.; Drenowatz, Clemens; Stodden, David F.; Pritchett, Kelly; Brodrick, Thaddus C.; Williams, Brittany T.; Goins, Justin M.; Torres-McGehee, Toni M. (Frontiers in Nutrition, 2021)
Background: Studies examining the physiological consequences associated with deficits in energy availability (EA) for male athletes are sparse. Purpose: To examine male athlete triad components; low energy availability (LEA) with or without an eating disorder risk (ED), reproductive hormone [testosterone (T)], and bone mineral density (BMD) in endurance-trained male athletes during different training periods. Methods: A cross-sectional design with 14 participants (age: 26.4 ± 4.2 years; weight: 70.6 ± 6.4 kg; height: 179.5 ± 4.3 cm; BMI: 21.9 ± 1.8 kg/m2) were recruited from the local community. Two separate training weeks [low (LV) and high (HV) training volumes] were used to collect the following: 7-day dietary and exercise logs, and blood concentration of T. Anthropometric measurements was taken prior to data collection. A one-time BMD measure (after the training weeks) and VO2max-HR regressions were utilized to calculate EEE. Results: Overall, EA presented as 27.6 ± 10.7 kcal/kgFFM·d-1 with 35% (n = 5) of participants demonstrating increased risk for ED. Examining male triad components, 64.3% presented with LEA (≤ 30 kcal/kgFFM·d-1) while participants presented with T (1780.6 ± 1672.6 ng/dl) and BMD (1.31 ±.09 g/cm2) within normal reference ranges. No differences were found across the 2 training weeks for EI, with slight differences for EA and EEE. Twenty-five participants (89.3%) under-ingested CHO across both weeks, with no differences between weeks. Conclusion: Majority of endurance-trained male athletes presented with one compromised component of the triad (LEA with or without ED risk); however, long-term negative effects on T and BMD were not demonstrated. Over 60% of the participants presented with an EA ≤ 30 kcal/kgFFM·d-1, along with almost 90% not meeting CHO needs. These results suggest male endurance-trained athletes may be at risk to negative health outcomes similar to mechanistic behaviors related to EA with or without ED in female athletes.